2021
DOI: 10.1109/access.2021.3056151
|View full text |Cite
|
Sign up to set email alerts
|

Research on Negative Bias Temperature Instability Effects Under the Coupling of Total Ionizing Dose Irradiation for PDSOI MOSFETs

Abstract: The degradation mechanisms for pMOSFETs from a 130 nm partially-depleted silicon on insulator (PDSOI) technology under the combined effects of total ionizing dose (TID) and negative bias temperature instability (NBTI) are investigated. The TID and NBTI related degradations show an opposite trend as gate oxide scaling, which implies the different traps are activated during irradiation and NBTI stress. The radiation-induced traps can affect the NBTI effect of pMOSFET, especially for the ON bias irradiation. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…Based on the PDSOI device, Peng et al investigated the impact of BOX Si+ implantation TID hardening technology on the NBTI effect [ 15 ] and their work showed that more damage-related traps exist near the gate oxide/silicon interface for the radiation-hardened device, which accelerates the threshold voltage shift during NBT stress. The impact of the TID effect on the NBTI effect of the PDSOI device was investigated in a further paper by Peng et al [ 16 ], and it was found that the irradiated device shows a smaller threshold voltage shift than the un-irradiated device under the same NBTI stress at the early stress stage, but the irradiation also increases the time exponent and leads to a significant reduction in the lifetime of the device. The influence of TID irradiation on the NBTI trap characteristics was also analyzed in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the PDSOI device, Peng et al investigated the impact of BOX Si+ implantation TID hardening technology on the NBTI effect [ 15 ] and their work showed that more damage-related traps exist near the gate oxide/silicon interface for the radiation-hardened device, which accelerates the threshold voltage shift during NBT stress. The impact of the TID effect on the NBTI effect of the PDSOI device was investigated in a further paper by Peng et al [ 16 ], and it was found that the irradiated device shows a smaller threshold voltage shift than the un-irradiated device under the same NBTI stress at the early stress stage, but the irradiation also increases the time exponent and leads to a significant reduction in the lifetime of the device. The influence of TID irradiation on the NBTI trap characteristics was also analyzed in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…These trap charges degrade device performance, which is referred to as the total ionizing dose (TID) effect. (1)(2)(3) The TID effect leads to threshold voltage drift, increased off-state leakage current, decreased transconductance, and other issues (4,5) up to the permanent failure of the circuit function. For nanoscale fully depleted silicon-on-insulator (FDSOI) devices, (6)(7)(8)(9)(10) the gate oxide layer may be very thin, (11)(12)(13) which makes the effect of gate oxygen trap charges generated by irradiation on device performance negligible.…”
Section: Introductionmentioning
confidence: 99%